Chronic Intermittent Ethanol Exposure and Withdrawal Alters (3α, 5α)‐3‐Hydroxy‐Pregnan‐20‐One Immunostaining in Cortical and Limbic Brain Regions of C57BL/6J Mice. (7th October 2014) - Maldonado‐Devincci, Antoniette M.; Cook, Jason B.; O'Buckley, Todd K.; Morrow, Danielle H.; McKinley, Raechel E.; Lopez, Marcelo F.; Becker, Howard C.; Morrow, A. Leslie
<x xml:space="preserve">Abstract</x> Background The GABAergic neuroactive steroid (3α, 5α)‐3‐hydroxy‐pregnan‐20‐one (3α, 5α‐THP; allopregnanolone) has been studied during withdrawal from ethanol (EtOH) in humans, rats, and mice. Serum 3α, 5α‐THP levels decreased, and brain levels were not altered following acute EtOH administration (2 g/kg) in male C57BL/6J mice; however, the effects of chronic intermittent ethanol (CIE) exposure on 3α, 5α‐THP levels have not been examined. Given that CIE exposure changes subsequent voluntary EtOH drinking in a time‐dependent fashion following repeated cycles of EtOH exposure, we conducted a time‐course analysis of CIE effects on 3α, 5α‐THP levels in specific brain regions known to influence drinking behavior. Methods Adult male C57BL/6J mice were exposed to 4 cycles of CIE to induce EtOH dependence. All mice were sacrificed and perfused at 1 of 2 time points, 8 or 72 hours following the final exposure cycle. Free‐floating brain sections (40 μm; 3 to 5 sections/region/animal) were immunostained and analyzed to determine relative levels of cellular 3α, 5α‐THP. Results Withdrawal from CIE exposure produced time‐dependent and region‐specific effects on immunohistochemical detection of 3α, 5α‐THP levels across cortical and limbic brain regions. A transient reduction in 3α, 5α‐THP immunoreactivity was observed in the central nucleus of the amygdala 8 hours after withdrawal from CIE (−31.4 ± 9.3%). Decreases in 3α, 5α‐THP immunoreactivity were observed 72 hours following withdrawal in the medial prefrontal cortex (−25.0 ± 9.3%), nucleus accumbens core (−29.9 ± 6.6%), and dorsolateral striatum (−18.5 ± 6.0%), while an increase was observed in the CA3 pyramidal cell layer of the hippocampus (+42.8 ± 19.5%). Sustained reductions in 3α, 5α‐THP immunoreactivity were observed at both time points in the lateral amygdala (8 hours −28.3 ± 12.8%; 72 hours −27.5 ± 12.4%) and in the ventral tegmental area (8 hours −26.5 ± 9.9%; 72 hours −31.6 ± 13.8%). Conclusions These data suggest that specific neuroadaptations in 3α, 5α‐THP levels may be present in regions of brain that mediate anxiety, stress, and reinforcement relevant to EtOH dependence. The changes that occur at different time points likely modulate neurocircuitry involved in EtOH withdrawal as well as the elevated drinking observed after CIE exposure.